Ars2‐containing bispecific, Fab‐ and IgG1‐format BAR‐bodies to target DLBCL cells. Issue 1 (27th December 2022) - Kiefer, Maximilian; Thurner, Lorenz; Bock, Theresa; Cetin, Onur; Kos, Igor; Lesan, Vadim; Kaddu‐Mulindwa, Dominic; Bittenbring, Joerg Thomas; Fadle, Natalie; Regitz, Evi; Hoth, Markus; Neumann, Frank; et al.
Abstract: Despite recent advances in the therapy of diffuse large B‐cell lymphoma, not otherwise specified (DLBCL), around 30% of patients develop refractory disease or relapse after first‐line treatment. Recently, Ars2 was reported as the auto‐antigenic target of the B‐cell receptor (BCR) in approximately 25% of activated B‐cell DLBCL cases. Ars2 could be used to specifically target B cells expressing Ars2‐reactive BCRs. However, the optimal therapeutic format to integrate Ars2 into has yet to be determined. To mimic therapeutic antibody formats, Ars2‐containing bispecific and IgG1‐like constructs (BCR antigens for reverse [BAR]‐bodies) were developed. Two bispecific BAR‐bodies connecting single‐chain antibodies against CD16 or CD3 to the BCR‐binding epitope of Ars2 were constructed. Both constructs showed strong binding to U2932 cells and induced effector cell‐dependent and selective cytotoxicity against U2932 cells of up to 44% at concentrations of 20 μg/ml. Additionally, IgG1‐format Ars2 BAR‐bodies were constructed by replacing the variable heavy‐ and light‐chain regions of a full‐length antibody with the Ars2 epitope. IgG1‐format Ars2 BAR‐bodies also bound selectively to U2932 and OCI‐Ly3 cells and induced selective cytotoxicity of up to 60% at 10 μg/ml. In conclusion, Ars2‐containing bispecific and IgG1‐format BAR‐bodies both are new therapeutic formats to target DLBCL cells.